The Influence of Word of Mouth Communication and Social Media Promotion on the Decision to Choose Bank Syariah Indonesia Savings Products at the Sidoarjo Jenggolo Branch : Pengaruh Komunikasi Word of Mouth dan Promosi Media Sosial Terhadap Keputusan Memilih Produk Tabungan Bank Syariah Indonesia di Cabang Sidoarjo - Pertiwi , Oktaviani; Rochmaniah, Ainur (Universitas Muhammadiyah Sidoarjo, 2025)
The aim of this research is to look at the influence of Word of Mouth communication and social media promotion on the decision to choose Bank Syariah Indonesia savings products at the Sidoarjo Jenggolo branch. The quantitative research method is the questionnaire data collection technique. The analysis technique used is Multiple Linear Regression analysis using the SPSS calculation application. The results of this research show that there is an influence of Word of Mouth communication and social media promotion in the decision to choose Bank Syariah Indonesia savings products at the Sidoarjo Branch with an R value of 0.932, which is included in the very strong influence category, and the contribution of these two variables is 86.6%. It is hoped that in this research BSI will improve good relationships with customers and for further research we can examine the role of public relations in improving BSI on social media.